The quiescent double barrier regime in the DIII-D tokamak - Doyle, E. J.; Baylor, L. R.; Burrell, K. H.; Casper, T. A.; DeBoo, J. C.; Ernst, D. R.; Garofalo, A. M.; Gohil, P.; Greenfield, C. M.; Groebner, R. J.; Hyatt, A. W.; Jackson, G. L.; et al. (Plasma physics and controlled fusion, 2001)
Experiments on the DIII-D tokamak have identified a new sustained high-performance operating mode, termed the quiescent double barrier (QDB) regime. The QDB regime combines internal transport barriers (ITBs) with a quiescent, edge localized mode (ELM)-free H-mode edge, termed QH-mode, giving rise to separate core and edge transport barriers. These double barriers have been maintained for {>}3.5 s (~25τE), demonstrating a long-pulse, quasi-steady-state capability. The combination of core ITBs and edge H-mode temperature pedestals results in high-performance plasmas; a βN H89 product of 7 has been maintained for 10 τE, other peak (non-simultaneous) parameters include Ti≤17 keV, βN≤2.9% m T MA-1, H89≤2.6, β≤3.8%, τE≤ 160 ms, and DD neutron rate Sn≤5.5×10¹⁵ s-1. These results address a major issue with tokamak plasmas: how to sustain long-pulse, high-performance H-mode plasmas without ELMs, yet retaining the density and impurity control hitherto provided by ELMs. In these QDB plasmas ELMs are replaced by continuous benign MHD activity in the edge, which enhances particle transport. A signature of operation with a QH-mode edge appears to be very large radial electric fields in the edge and scrape-off layer (SOL). In the core, simulations and modelling replicate many of the features of the observed transport and fluctuation behaviour, including the ion temperature profile and turbulence correlation lengths. Slow high-Z impurity accumulation (τ ≥ 500 ms) is observed in the centre of many QDB plasmas, and is the subject of ongoing analysis. To date the QDB regime has only been obtained in plasmas with counter-NBI (injection anti-parallel to the plasma current), and with divertor cryopumping to control the density.